Perioperative Ethics and Patient Safety - Wichsová, Jana; Horáková, Andrea (Lumen publishing house, 2018)
Perioperative teams are focused on professional and safe patient care. The most important tool throughout the perioperative process is just health care workers, and quality of their care, despite the facts that they use a number of tools: construction arrangement of operating rooms, modern equipment and instruments, new materials, drugs and sophisticated diagnostic methods and practices based on scientific evidence,. Research demonstrates that poor quality care is also unethical. If the health care professionals break safety and hygienic policy, they also break the ethics of health care workers. Because they have an adequate knowledge of safe and hygienic patient care in the operating room.
Etika perioperační péče a bezpečnost pacienta
Keywords: Perioperative care; safety; patient safety; medical ethics; nursing ethics; Perioperační péče; bezpečnost pacienta; lékařská etika; ošetřovatelská etika